Структура та рівні культури професійного спілкування як інваріанта професійної психологічної культури - Улунова, Г. (Світогляд - Філософія - Релігія, 2011)
У статті аналізуються структура та рівні культури професійного спілкування як інваріанта професійної психологічної культури, яка, у свою чергу, є інваріантом професійної культури. Робляться висновки, що професійна культура, професійна психологічна культура та культура професійного спілкування мають універсальні структурно-рівневі особливості. The structure of professional communication culture as an invariant of professional psychological culture that at the same time is an invariant of professional culture is analysed in the article. It is concluded that professional culture, professional psychological culture and professional communication culture are characterised by similar structural peculiarities. Cognitive, operational, value and sense components are the basic ones for a structure of any culture. A structure of every subordinate kind of culture is a concretized variant of structure of culture of a higher level. Determination of culture levels and their content characteristics directly reflects a subject of investigation (kind of culture) and also identifies conceptual views of a researcher.